Reasons for Laser in Situ Keratomileusis in China: A Qualitative Study. Issue 3 (March 2019) - Xu, Yanjiao; Li, Shunping; Gao, Zhongchun; Nicholas, Stephen
Abstract : SIGNIFICANCE: Myopia is a major health issue in East Asian countries, especially in China. By identifying Chinese patients' motivations for laser in situ keratomileusis (LASIK) surgery, our results are expected to help clinicians counsel patients before LASIK surgery and to maximize patients' post-operative LASIK surgery satisfaction, improving the quality of LASIK surgery services. PURPOSE: Laser in situ keratomileusis has become a popular type of refractive surgery for the correction of myopia worldwide. This study uses qualitative inquiry approaches to understand the motives and processes of patients' LASIK surgery decision making. METHODS: A purposive sample of 45 patients who had decided to undergo LASIK was recruited. Our qualitative study used in-depth interviews and used content analysis to interpret the data. RESULTS: Among 45 participants, 48.9% reported that career requirements were the most important reason for seeking LASIK surgery. The inconvenience of wearing glasses or lenses during activities of daily life was also a primary motive. Improving facial appearance was a main reason for female but not male respondents. Potential complications of spectacles and contact lenses in addition to maturation of LASIK technology were also reported motives to seek surgery. Participants gave multiple, overlapping reasons for LASIK surgery. CONCLUSIONS: These findings suggest that motives to seek LASIK surgery are not only a desire to correct refractive error but also social factors and confidence in improved surgical technology. The implications for clinicians are to be aware of these multiple motives for LASIK to improve the quality and effectiveness of health services for myopia patients.